Соціально-економічні та соціокультурні процеси в містах Наддніпрянської України в 1785–1917 рр.: історіографія - Бондаренко, О. В.; Bondarenko, A. (Університет Григорія Сковороди в Переяславі, 2021)
Підкреслено, що проблема визначення поняття «місто», його типології та функцій не завжди мала дослідницький характер. Адже надання поселенню нового адміністративного статусу відчутно підвищувало його значущість, збільшувало права та свободи міського самоврядування, сприяло економічному розвитку, розміщенню адміністративних органів, отриманню замовлень від держави тощо. Тож зрозуміле прагнення місцевих еліт до надання їхньому поселенню статусу міста. Згодом виникає і чисто дослідницький інтерес статистиків, істориків, географів, представників інших наук, які виробили численні підходи до визначення та типології міста, що залежали передусім від наукової спеціалізації та світоглядних позицій конкретного вченого та специфіки їхнього творчого бачення. Схарактеризовано здобутки учених в обґрунтуванні концептуальних засад історії міст. Визначено внесок науковців в осмислення становлення та еволюції міського самоврядування, соціально-економічного та соціокультурного розвитку міст. З’ясовано особливості історіографічної інтерпретації проблеми в науковій літературі останньої чверті ⅩⅧ – початку ⅩⅩⅠ ст. та зміни у її дослідженні в різні історіографічні етапи. Визначені головні чинники, які впливали на розвиток досліджень з порушеної проблеми. Серед найменш розроблених в історіографії питань історії соціальноекономічних та соціокультурних процесів у містах Наддніпрянської України в 1785–1917 рр., які потребують подальшого вивчення виокремлено такі: питання становлення та розвитку міського самоврядування; місце міських органів самоврядування у системі губернських та повітових владних державних структур; взаємозв’язки міських фінансових та державних інституцій; повсякдення чиновників міських органів самоврядування; з’ясування їхньої ролі у громадському та культурному житті міських громад. Перспективними напрямами дальшого вивчення порушеної проблеми можуть бути комплексні історичні та історіографічні дослідження історії соціальноекономічних процесів в українських містах з використанням компаративного інструментарію; студії з соціокультурного розвитку міського соціуму, зокрема повсякдення містян, менталітет міських верств; вивчення історії корпоративних купецьких товариств та органів самоврядування купецтва; характеристика соціально-психологічного портрету міських прошарків; внутрішньосімейні стосунки у купецькій та міщанській родині; традиції сімейного виховання і освіти, ціннісні орієнтири; організація дозвілля і розваг у купецькому та міщанському середовищі. The practical significance of the dissertation work lies in the fact that the results obtained, substantiated conclusions and practical recommendations significantly expand modern knowledge on the history and historiography of socioeconomic and socio-cultural processes in the cities of Dnieper Ukraine in 1785- 1917. And accordingly, they will contribute to the intensification of research both on this issue and related and related topics. The provisions and conclusions of the dissertation work can be used in the lecture and methodological support of academic disciplines for applicants for higher education in the specialty "History and Archeology", in particular, "Historiography of the History of Ukraine", "Historical Regional Studies", "Historical Urban Studies", "Modern History of Ukraine" ... The relevance of the topic of the dissertation is substantiated, the purpose, tasks of scientific research, object and subject of research are formulated, its connection with scientific programs is noted, chronological and geographical borders are defined, scientific novelty and practical value of the received results are outlined, information on approbation of research results . Analysis of historiographical research on the history of socio-economic and socio-cultural processes in the cities of Dnieper Ukraine in 1785-1917 showed that this topic has not yet become the subject of a special generalizing historiographical study. Only some aspects of this complex problem have become the subject of research, which necessitates its in-depth and comprehensive study. In the dissertation for the first time in historical science the state and tendencies of more than 230 years of research of history of social and economic and sociocultural processes in the cities of Dnieper Ukraine in 1785–1917 are analyzed in detail. 12 The leading stages, directions and specific features of research of a theme are defined. The periodization of the problem is carried out in accordance with the development of historical thought and modern theoretical and methodological foundations of historiography. There are three main historiographical periods of scientific development of the problem: imperial - the end of the eighteenth - beginning of the twentieth century; Soviet - 1920s - 1991 and modern - 1991-2021, which characterize the priority trends of historiography in the study of urban history. The source base for the period from the last quarter of the 18th century has been identified, analyzed, systematized and classified. by 2021, its information potential has been revealed. A wide range of new historiographical sources has been introduced into scientific circulation, on the basis of which key aspects of the researched problem are considered. A wide source base made it possible to analyze the reflection in the scientific literature of the main directions of socio-economic and socio-cultural processes in the cities of the Dnieper region during the imperial era. It is noted that the study is based on the integrated use of the principles of historicism, objectivity, comprehensiveness, systemicity, continuity. A set of general scientific, interdisciplinary and specific historical methods was used to achieve the purpose of the study. The use of a wide range of methods of historiographical analysis and synthesis, problem-chronological, comparative, genetic, retrospective, contributed to the comprehensive solution of the dissertation tasks. Their choice is determined by the theme of the dissertation, its structure and the specifics of modern methodological approaches, in particular those borrowed by historians from other scientific disciplines. However, despite the variety of research methods, the key was the problem-chronological method, which allowed to clearly outline the ways of general accumulation of historical knowledge of various semantic aspects of the problem. These methodological principles made it possible to trace the evolution of historiographical discourse during the last quarter of the eighteenth and early twenty-first centuries. and its structural and institutional forms. 13 It is proved that among the important and insufficiently studied methodological problems of the history of the cities of Dnieper Ukraine in 1785– 1917 is the scientific definition of its concept, typology and functional purpose. After all, a significant role in the study of cities belongs to the conceptual and terminological apparatus. One of its basic concepts is "city", which, along with others, being in close connection, and forms a terminological and conceptual system used by historical science and historical urban planning in particular. The problem of the content of this concept arose at least from the first half of the XIX century. and is due to the coexistence of various forms of urban settlements and the reflection of the phenomenon of the city in the public consciousness, administrative and demographic statistics, whence it was introduced into science. It is emphasized that the problem of defining the concept of "city", its typology and functions has not always been research. After all, granting the settlement a new administrative status significantly increased its significance, increased the rights and freedoms of municipal self-government, contributed to economic development, placement of administrative bodies, receiving orders from the state, and so on. Therefore, the desire of local elites to give their settlement the status of a city is understandable.
Socio-economic and socio-cultural processes in the cities of the Dnieper Ukraine in 1785-1917: historiograp
Keywords: історіографія; Наддніпрянська Україна; міста; міське самоврядування; міські фінанси; промисловість; торгівля; historiography; Dnieper Ukraine; city government